Tel Shiqmona during the Iron Age: A first glimpse into an ancient Mediterranean purple dye ‘factory’ - Golan Shalvi; Naama Sukenik; Paula Waiman-Barak; Zachary C. Dunseth; Shay Bar; Sonia Pinsky; David Iluz; Zohar Amar; Ayelet Gilboa (PLoS ONE, 2025)
Purple-dyed textiles, primarily woolen, were much sought after in the Ancient Near East and the Mediterranean, and they adorned the powerful and wealthy. It is commonly assumed that in antiquity, purple dye—extracted from specific species of marine mollusks—was produced in large quantities and in many places around the Mediterranean. But despite numerous archaeological excavations, direct and unequivocal evidence for locales of purple-dye production remains very limited in scope. Here we present Tel Shiqmona, a small archaeological tell on Israel’s Carmel coast. It is the only site in the Near East or around the Mediterranean—indeed, in the entire world—where a sequence of purple-dye workshops has been excavated and which has clear evidence for large-scale, sustained manufacture of purple dye and dyeing in a specialized facility for half a millennium, during the Iron Age (ca. 1100–600 BCE). The number and diversity of artifacts related to purple dye manufacturing are unparalleled. The paper focuses on the various types of evidence related to purple dye production in their environmental and archaeological contexts. We utilize chemical, mineralogical and contextual analyses to connect several categories of finds, providing for the first time direct evidence of the instruments used in the purple-dye production process in the Iron Age Levant. The artifacts from Shiqmona also serve as a first benchmark for future identification of significant purple-dye production sites around the Mediterranean, especially in the Iron Age.